2001
DOI: 10.1021/bi0101749
|View full text |Cite
|
Sign up to set email alerts
|

Structural Studies in Solution of the Recombinant N-Terminal Pair of Short Consensus/Complement Repeat Domains of Complement Receptor Type 2 (CR2/CD21) and Interactions with Its Ligand C3dg

Abstract: Human complement receptor type 2 (CR2, CD21) is a cell surface receptor that binds three distinct ligands (complement C3d, Epstein-Barr virus gp350/220, and the low-affinity IgE receptor CD23) via the N-terminal two of fifteen or sixteen short consensus/complement repeat (SCR) domains. Here, we report biophysical studies of the CR2 SCR 1-2 domain binding to its ligand C3dg. Two recombinant forms of CR2 containing the SCR 1-2 and SCR 1-15 domains were expressed in high yield in Pichia pastoris and baculovirus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
91
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 47 publications
12
91
0
Order By: Relevance
“…3). This finding is consistent with solution studies, which also suggest a more extended conformation of this CD21 fragment (42).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…3). This finding is consistent with solution studies, which also suggest a more extended conformation of this CD21 fragment (42).…”
Section: Resultssupporting
confidence: 92%
“…4B). Third, the CD21͞C3d interface is surprisingly small for an interaction with nanomolar affinity (42). Although the buried surface area of the complex was reported as 1,400 Å 2 (17), our own calculations using the .…”
Section: Resultsmentioning
confidence: 83%
“…Subsequent biochemical studies were consistent with a requirement for both SCR1 and SCR2 in the interaction with C3d (37,49). However, contrary to suggestions in earlier studies, the x-ray co-crystal structure showed only SCR2 to be in contact with C3d (33).…”
Section: Discussionsupporting
confidence: 68%
“…Expression and Purification of Recombinant Proteins-Human CR2 SCR1-2 for NMR studies was expressed in Pichia pastoris using a BioFlo 110 Fermenter (New Brunswick Scientific, Edison, NJ), as previously described (37). Briefly, a single colony was grown in 5 ml of Pichia basal salt medium containing 1% glycerol (BMG) overnight at 30°C and 250 rpm, expanded to 50 ml of BMG (24 h), and finally expanded to 300 ml of BMG (24 h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation